PENDIDIKAN EKOLOGI BAGI UMAT DI STASI SANTA ANA MARIA SIMPANG NANENG PAROKI SANTO PETRUS DAN PAULUS AMPAH - Bernardus Bani; Timotius Tote Jelahu; Fransiskus Janu Hamu (Sepakat : Jurnal Pastoral Kateketik, 2019)
The aim of this research is to know how far the ecology education for the parishoners in the region of St.Ana Maria, Simpang Naneng in St.Petrus an& Paulus parish, Ampah. Ecological education can help people in maintaining and treating the environment properly. This is descriptive qualitative research. Data obtained by observation, interview methods and documentation. The research steps include conversations with informants, informant profiles, determining themes, reflections, implications, synthesis, prospects or possibilities that occur. Information are pastoral officers, parish priests and some parishioners The results of the study showed that the parishioner’s ecological knowledge was still lacking. It is caused by the level of human resources and also the limitation of reporting about ecological education by pastoral officers to the parishioner. In particular, the church can explain ecological education through catechesis for people in the region of St. Ana Maria, Simpang Naneng, st.petrus and Paulus parish, Ampah.